2020
DOI: 10.1038/s41598-020-60688-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a combination of transcription factors that synergistically increases endothelial cell barrier resistance

Abstract: Endothelial cells (ECs) display remarkable plasticity during development before becoming quiescent and functionally mature. EC maturation is directed by several known transcription factors (TFs), but the specific set of TFs responsible for promoting high-resistance barriers, such as the blood-brain barrier (BBB), have not yet been fully defined. Using expression mRNA data from published studies on ex vivo ECs from the central nervous system (CNS), we predicted TFs that induce high-resistance barrier properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Moreover, noncanonical Wnt signaling may contribute to the establishment of the BBB phenotype (Pinzón-Daza et al, 2014). Sox17 has been identified as a major target of the β-catenin pathway in endothelial cells (Corada et al, 2019), together with Lef1 and Ets1 (Roudnicky et al, 2020). These Wnt-regulated transcription factors up-regulate the transcription of several junctional proteins, including VE-cadherin and claudin-5 (Roudnicky et al, 2020), possibly involved in the repair of the BSCB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, noncanonical Wnt signaling may contribute to the establishment of the BBB phenotype (Pinzón-Daza et al, 2014). Sox17 has been identified as a major target of the β-catenin pathway in endothelial cells (Corada et al, 2019), together with Lef1 and Ets1 (Roudnicky et al, 2020). These Wnt-regulated transcription factors up-regulate the transcription of several junctional proteins, including VE-cadherin and claudin-5 (Roudnicky et al, 2020), possibly involved in the repair of the BSCB.…”
Section: Discussionmentioning
confidence: 99%
“…Sox17 has been identified as a major target of the β-catenin pathway in endothelial cells ( Corada et al, 2019 ), together with Lef1 and Ets1 ( Roudnicky et al, 2020 ). These Wnt-regulated transcription factors up-regulate the transcription of several junctional proteins, including VE-cadherin and claudin-5 ( Roudnicky et al, 2020 ), possibly involved in the repair of the BSCB. Furthermore, claudin-5 is dynamically internalized and stored in intracellular vesicles upon inflammatory stimuli and trafficked back to the cell surface when the inflammatory signaling is subsided ( Stamatovic et al, 2003 , 2006 , 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…To do this, we measured macromolecular fluxes using specific dextran molecular weights chosen based on previous work investigating brain and retinal microvasculature permeability. [30][31][32][33][34] In the case of a tight endothelial barrier, tracers were retained on the luminal side of the tube, whereas tracers rapidly diffused into the matrix over 20 min in the case of a leaky barrier. Image analysis was used to quantify the leakage score (a metric that is specific to this system) and the apparent permeability (P a ; standardized metric of barrier function for comparison to other models; Figure 2a,b and Figure S2, Supporting Information).…”
Section: Microfabricated Retinal Microvasculature-on-a-chip Recapitulmentioning
confidence: 99%
“…A shift from the co-differentiation protocol to direct BCECs generation was achieved by using chemically defined factors (Grifno et al, 2019;Praca et al, 2019;Qian et al, 2017). Recent advancements have been focused on the overexpression of transcription factors in upregulating BBB phenotypes (Roudnicky et al, 2020). Here, Roudnicky et al identified 17 transcription factors, including among others TAL1, SOX7, SOX18, ETS1, and LEF1, to improve the direct differentiation of vascular endothelial cells and analyzed them using gain-of-function assays (Patsch et al, 2015;Roudnicky et al, 2020).…”
Section: Comparison Of Differentiation Methods and Cellular Charactermentioning
confidence: 99%
“…A shift from the co‐differentiation protocol to direct BCECs generation was achieved by using chemically defined factors (Grifno et al., 2019; Praca et al., 2019; Qian et al., 2017). Recent advancements have been focused on the overexpression of transcription factors in upregulating BBB phenotypes (Roudnicky et al., 2020). Here, Roudnicky et al.…”
Section: Current Technological Status In Hipsc‐derived Bbb Modelingmentioning
confidence: 99%